pengaruh PENGARUH CITRA MEREK DAN LOKASI KRISNA OLEH-OLEH KHAS BALI TERHADAP MINAT BELI KONSUMEN DI RESTORAN BERLIN GASTRO KITCHEN & POOL BAR, KUTA, BADUNG - Arcana, I nyoman; Budiani, Ni Putu Ariesta; Massenga, Lidjah Magdalena; Juniari, Kadek Eni (JURNAL BISNIS HOSPITALITI, 2023)
This study aims to determine the effect of Brand Image and Location on Consumer Buying Interest. The population in this study were visitors to the Berlin Gastro restaurant and Krisna Bypass Bali Bypass Ngurah Rai with a sample of 66 people. The data analysis techniques used in this study are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, F Test, t Test and Coefficient of Determination. Based on the results of the study, it can be seen that: (1) Brand Image has a positive and significant effect on consumer buying interest at the Berlin Gastro restaurant, where the regression coefficient is 0.430 and the significance value is 0.002. (2) location has a positive and significant effect on consumer buying interest at the Berlin Gastro restaurant, where the regression coefficient is 0.417 and the significance value is 0.003. The results of this study recommend that restaurant managers in attracting consumer buying interest are expected to partner with other companies that already have a strong brand image and strategic location as a strategy to increase consumer buying interest.